THE ROLE OF SENSES, EMOTIONS AND THE PRINCIPLES OF THE EXPERIENCE ECONOMY IN THE CREATIVE INDUSTRIES. - Eglīte, Žanete (Culture Crossroads, 2021)
Sensory features of products and services affect emotions, memories, perception, choices and consumption. The creation of new emotions or emphasising of existing ones can increase the appeal of the product or service. Furthermore, it is important for the creative industries to create products and services that inspire, include and reflect consumer values. The creative industries - which include advertising, architecture, arts and crafts, design, fashion, film production, video, photography, music, the performing arts, publishing, research and development, software and computer game development, and electronic publishing, as well as TV and radio - are elements of the creative economy. Creativity is also one of the drivers of the experience economy. According to theorists of experience economics Joseph Pine and James Gilmore, the most prolific experiences are authentic, remain in the memory and change human notions by stimulating all five senses (vision, hearing, smell, taste and touch), provoking emotions and feelings, and allowing people to participate and be involved. The research question of this paper is as follows: how are senses and emotions linked with experiences, when they are used in the development of creative products and services? Therefore, this paper proposes a theoretical review of how to incorporate senses and sensory design into a more comprehensive understanding within the creative economy, as well as the experience economy.